COVID-19 vaccine selfie: a modest endeavor to increase vaccine acceptance. Issue 2 (1st February 2023) - Ittefaq, Muhammad; Ahmad Kamboh, Shafiq; Abwao, Mauryne
Abstract: Drawing on the theory of normative conduct, which suggests that individuals get motivated by what most people do, this commentary argues that the COVID-19 vaccine selfies carry a reasonable potential to encourage the vaccine acceptance behavior among social media users. Despite having both its proponents and critics, the COVID-19 vaccine selfie could positively shape the public response to the vaccines by highlighting health, joy, and optimism. While discussing different strategies for taking and posting an effective selfie, this article recommends sharing vaccine selfies online as it is a powerful tool to send a message to anti-vaxxers that the COVID-19 vaccines are safe and effective.